2017
DOI: 10.1186/s40657-017-0076-3
|View full text |Cite
|
Sign up to set email alerts
|

Incubation strategies of the Black-necked Crane (Grus nigricollis) in relation to ambient temperature and time of day

Abstract: Background:The behavior of cranes reflects many of their survival strategies, but little has been known of the incubation strategies of cranes, in which both parents share incubation duties, in response to cold temperatures in alpine environments. The lack of information may restrict the effective conservation of the threatened Black-necked Crane (Grus nigricollis), a biparental bird nesting in high elevation wetlands. Methods:We directly observed and used infrared video cameras from 2014 to 2015 to study the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…These findings further suggest that the timescales we use to measure thermal change and behavioral modification alter how we view the plasticity of organismal behavior to the thermal environment. Multiple studies have shown that the relationship between temperature and the average lengths of off-bouts predicts avian reproductive success (4851). Approaches considering averaged conditions can contextualize general trends in behavior (52,53), but as we show above, only examining behavior in this way risks missing the relationship between the rate of thermal change and organismal behavior.…”
Section: Discussionmentioning
confidence: 99%
“…These findings further suggest that the timescales we use to measure thermal change and behavioral modification alter how we view the plasticity of organismal behavior to the thermal environment. Multiple studies have shown that the relationship between temperature and the average lengths of off-bouts predicts avian reproductive success (4851). Approaches considering averaged conditions can contextualize general trends in behavior (52,53), but as we show above, only examining behavior in this way risks missing the relationship between the rate of thermal change and organismal behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In arid climates such as in the San Luis Valley of Colorado, temperatures can vary by more than 20 °C throughout the day (Mix et al 2011). Daily variation in temperature has been shown to influence nest attendance patterns in other bird species including Wild Turkeys Meleagridis gallopavo (Spohr 2001), Black‐necked Cranes Grus nigricollis (Zhang et al 2017) and Carolina Chickadees Poecile carolinensis (Walters et al 2016). In addition, eggs become increasingly susceptible to fluctuations in temperature as they approach hatching, necessitating increased attentiveness or strategic timing of nest recesses to correspond with high ambient temperatures (Romanoff & Romanoff 1949, Hepp et al 2005, Burnam et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The black-necked crane (Grus nigricollis; Figure 1), the only alpine crane species endemic to the plateaus, primarily breeds in scattered sites on the Qinghai-Tibetan Plateau in south-central China (Archibald et al, 2020), and winters in southern and eastern parts of the plateau (Bishop et al, 1998;Jia et al, 2019), and on the Yunnan-Guizhou Plateau in China (Archibald et al, 2020;Li, 2014;Zhang et al, 2014). The species has recently been reclassified from "Vulnerable (VU)" to "Near Threatened (NT)" by the International Union for Conservation of Nature (IUCN, 2020) due to recent growth in its population, with an estimated global population of 17,389-17,610 in the wild (Chen et al, 2023).…”
Section: Introductionmentioning
confidence: 99%